2010
DOI: 10.1248/yakushi.130.737
|View full text |Cite
|
Sign up to set email alerts
|

Beta-Asarone Attenuates Neuronal Apoptosis Induced by Beta Amyloid in Rat Hippocampus

Abstract: Neurodegenerative disorders, such as Alzheimer's disease (AD), is associated with the loss of neuronal cells, and it has been suggested that apoptosis is a crucial pathway in neuronal loss in AD patients. Recent evidence suggests that amyloid beta peptide (Ab) induces neuronal apoptosis in the brain and in primary neuronal cultures. In this study, we investigated the impact of b-asarone against the apoptosis induced by Ab in rat hippocampus. The results showed that intrahippocampal injections of Ab (1 42) cau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(35 citation statements)
references
References 41 publications
0
34
0
1
Order By: Relevance
“…For the first time we reported the growth inhibitory effect of β-asarone on LoVo cells by inducing the cells apoptosis, which might extend its potential usage. Liu et al (2010) and Zou et al (2011) have reported that beta-asarone can attenuate neuronal apoptosis by amyloid in rat hippocampus. Their results had shown that beta-asarone has the ability to attenuate the apoptosis, which is different from ours.…”
Section: Discussionmentioning
confidence: 99%
“…For the first time we reported the growth inhibitory effect of β-asarone on LoVo cells by inducing the cells apoptosis, which might extend its potential usage. Liu et al (2010) and Zou et al (2011) have reported that beta-asarone can attenuate neuronal apoptosis by amyloid in rat hippocampus. Their results had shown that beta-asarone has the ability to attenuate the apoptosis, which is different from ours.…”
Section: Discussionmentioning
confidence: 99%
“…It has effects on multi-target genes in mouse brain [8] . It can obviously increase the expression of c-fos in epilepsy rat brain [9] , and attenuate neuronal apoptosis induced by β-amyloid in rat hippocampus and in PC12 cells [10,11] . But it may also have side effects.…”
Section: Observation Of Ultrastructural Morphology Of Autophagosomementioning
confidence: 99%
“…It helps to maintain cell homeostasis [1][2][3] , but excessive autophagy may also leads to autophagic neuron death and apoptosis [4][5][6] . β-asarone, one of chief constituents from Acorus Tatarinowii Schott, can easily pass through the blood brain barrier [7] , and shows various neuroprotective effects such as protecting neuron against apoptosis [8][9][10][11] . However, the effect of β-asarone on autophagy in a model of ischemic stroke in vitro is rarely reported.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, RAGE is believed to be an important cellular factor for the pathogenesis of AD and is served as a new target for AD therapy (Zlokovic 2008;Yan et al 2009Yan et al , 2012. b-asarone, the essential component of Acori graminei rhizoma (AGR), can easily pass through BBB (Fang et al 2012) and exert neuroprotective effects in both vivo and vitro AD models (Zou et al 2011;Liu et al 2010;Geng et al 2010). Our previous study has proven that b-asarone could reduce neuronal apoptosis and improve memory deficits in Tg AD-model mice (Wei et al 2013).…”
Section: Introductionmentioning
confidence: 99%